Dose-responses to lysine, valine, and isoleucine and the effects of monosodium glutamate on nursery pigs - Clark, Anne Bonner (Kansas State University, 2016)
Six experiments using a total of 2,974 nursery pigs were used to determine the effects of monosodium glutamate (MSG) and amino acids (AA) on nursery pig growth performance. Experiments 1 and 2 evaluated increasing dietary MSG for nursery pigs. Increasing dietary MSG up to 2% without balancing for sodium and chloride content decreased nursery pig performance, and feeding sodium levels equivalent to 1% MSG also decreased performance. When sodium and chloride were balanced, there were marginal effects of increasing dietary MSG on pig performance. Experiment 3 was conducted to determine the standardized ileal digestible (SID) lysine (Lys) requirement for pigs weighing 7- to 11- kg. The SID Lys requirement was estimated to be 1.45% and greater than 1.60% depending on the statistical model applied for both ADG and G:F. This experiment served to validate the SID Lys requirement for use in formulating diets for the subsequent experiments. Experiment 4 evaluated increasing SID valine (Val) to Lys ratio for nursery pigs weighing 7- to 10- kg. A SID Val:Lys ratio of 62.9% optimized ADG. Maximum feed efficiency (G:F) was captured using 71.7% SID Val:Lys ratio, however, 99% of maximum was achieved with SID Val at 64.4% of Lys. For ADFI, maximum performance was at 74% SID Val:Lys ratio, with 99% of maximum intake achieved at 68%. Experiments 5 and 6 investigated increasing SID isoleucine (Ile) to Lys ratio for 6- to 11- kg pigs. When ADG and ADFI were modeled, broken-line models reported maxima of 52.0% Ile:Lys ratio while quadratic models were as high as 64% of Lys.
Keywords: Lysine; Valine; Isoleucine; Monosodium glutamate; Nursery pigs; Amino acids